Body mass index at diagnosis and survival among colon cancer patients enrolled in clinical trials of adjuvant chemotherapy. Issue 8 (10th January 2013) - Sinicrope, Frank A.; Foster, Nathan R.; Yothers, Greg; Benson, Al; Seitz, Jean Francois; Labianca, Roberto; Goldberg, Richard M.; DeGramont, Aimery; O'Connell, Michael J.; Sargent, Daniel J.; for the Adjuvant Colon Cancer Endpoints (ACCENT) Group
Abstract BACKGROUND: Although obesity is an established risk factor for developing colon cancer, its prognostic impact and relation to patient sex in colon cancer survivors remains unclear. METHODS: The authors examined the prognostic and predictive impact of the body mass index (BMI) in patients with stage II and III colon carcinoma (N = 25, 291) within the Adjuvant Colon Cancer Endpoints (ACCENT) database. BMI was measured at enrollment in randomized trials of 5‐fluorouracil–based adjuvant chemotherapy. Association of BMI with the time to recurrence (TTR), disease‐free survival (DFS), and overall survival (OS) were determined using Cox regression models. Statistical tests were 2‐sided. RESULTS: During a median follow‐up of 7.8 years, obese and underweight patients had significantly poorer survival compared with overweight and normal‐weight patients. In a multivariable analysis, the adverse prognostic impact of BMI was observed among men but not among women (Pinteraction = .0129). Men with class 2 and 3 obesity (BMI ≥35.0 kg/m2) had a statistically significant reduction in DFS (hazard ratio [HR], 1.16; 95% confidence interval [CI], 1.01‐1.33; P = .0297) compared with normal‐weight patients. Underweight patients had a significantly shorter TTR and reduced DFS (HR, 1.18; 95% CI, 1.09‐1.28; P < .0001) that was more significant among men (HR, 1.31; 95% CI, 1.15‐1.50; P < .0001) than among women (HR, 1.11; 95% CI, 1.01‐1.23; P = .0362; Pinteraction = .0340). BMI was not predictive of a benefit from adjuvant treatment. CONCLUSIONS: Obesity and underweight status were associated independently with inferior outcomes in patients with colon cancer who received treatment in adjuvant chemotherapy trials. Cancer 2013. © 2013 American Cancer Society.